Algorithmic Differentiation of Society – a Luhmann Perspective on the Societal Impact of Digital Media - Taekke, Jesper (Journal of Sociocybernetics, 2022)
The aim of this article is to put forward Luhmann’s theory of social differentiation as the way society as a social system has organized itself internally after it has differentiated itself out from its external environment. The question discussed is if we are facing a new form of differentiation triggered by digital media. To answer the question, the article puts forward Luhmann´s theory and the historical forms of differentiation he described. After that the article shows how the triggering factor, in a non-deterministic way, for Luhmann is communication media. A new differentiation form emerges when the dynamic and complexity of society has increased to such an extent, i.e., other forms of differentiation have grown in latency, that a new form can take over. After the introduction to the theory and the interpretations of it, it is discussed if and how a new form of differentiation is under development. The discussion circles around how to interpret contemporary developments as signs of how the new differentiation form works. The article concludes that functional differentiation is surpassed by a new basic form of differentiation which is the algorithmic differentiation of society.